The coding manual for qualitative researchers - Saldaña, Johnny (SAGE, 2016)
An introduction to codes and coding -- Writing analytic memos about narrative and visual data -- First cycle coding methods -- After first cycle coding -- Second cycle coding methods -- After second cycle coding